2021
DOI: 10.1186/s12939-020-01346-6
|View full text |Cite
|
Sign up to set email alerts
|

What do you mean by engagement? – evaluating the use of community engagement in the design and implementation of chronic disease-based interventions for Indigenous populations – scoping review

Abstract: Background Indigenous populations have remained strong and resilient in maintaining their unique culture and values, despite centuries of colonial oppression. Unfortunately, a consequential result of facing years of adversity has led Indigenous populations to experience a disproportionate level of poorer health outcomes compared to non-Indigenous populations. Specifically, the rate of Indigenous chronic disease prevalence has significantly increased in the last decade. Many of the unique issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…However, it was less common for interventions to be owned, delivered and/or directed by the community themselves. Similar findings to this review have also been reported in a recent scoping review evaluating community engagement in the design and implementation of chronic disease-based interventions for Indigenous populations [ 110 ]. In that review, Wali and colleagues reported that despite the agreed need to engage with Indigenous communities to support intervention engagement, few meaningfully consulted the community through all levels of intervention design and delivery [ 110 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it was less common for interventions to be owned, delivered and/or directed by the community themselves. Similar findings to this review have also been reported in a recent scoping review evaluating community engagement in the design and implementation of chronic disease-based interventions for Indigenous populations [ 110 ]. In that review, Wali and colleagues reported that despite the agreed need to engage with Indigenous communities to support intervention engagement, few meaningfully consulted the community through all levels of intervention design and delivery [ 110 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings to this review have also been reported in a recent scoping review evaluating community engagement in the design and implementation of chronic disease-based interventions for Indigenous populations [ 110 ]. In that review, Wali and colleagues reported that despite the agreed need to engage with Indigenous communities to support intervention engagement, few meaningfully consulted the community through all levels of intervention design and delivery [ 110 ]. Several authors have similarly argued that adopting participatory design approaches involving Indigenous communities as co-designers and decision-makers from the outset of intervention development is critical to achieve meaningful and lasting change [ 111 113 ].…”
Section: Discussionsupporting
confidence: 89%
“…And third, it is useful to consider contextual issues across all levels of a socio-ecological framework (individual, interpersonal, organizational, community, policy) [52]. Table 1 summarizes reviews of equity-relevant studies describing essential implementation contextual elements for interventions among disadvantaged populations and lowresource settings [55][56][57][58][59].…”
Section: Inadequate Attention To Contextmentioning
confidence: 99%
“…e engagement of both participants and local institutions to promote IK with initial transformative learning experiences demonstrates the potential for creating a path of critical consciousness [22]. More commonly, community engagement approaches use community members at the centre of the process to empower indigenous voices, strengthen community capacity, and promote meaningful change [23]. Educational communities and their actors, therefore, are encouraged to use their professional judgment and to reprogram educational content in terms of its scope, sequence, progression, continuity, and approach to teaching and evaluating [24].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Participation of the local community in the provision of the AE is crucial for both the success of the collaboration and the achievement of the overall objective of the program [17]. Two dominant themes related to community engagement such as adapting to a cultural context and inclusion of community outreach [23] can be used within a specific program provision, especially in IK-based on AE delivery. erefore, engaging the local community in the process of their learning is the groundwork for any stakeholders.…”
Section: Engaging Local Communities To Develop and Preservementioning
confidence: 99%